2017
DOI: 10.1007/s00216-017-0250-9
|View full text |Cite
|
Sign up to set email alerts
|

Determination of volatile compounds in cider apple juices using a covalently bonded ionic liquid coating as the stationary phase in gas chromatography

Abstract: A chromatographic method for the separation of volatile compounds in Asturian cider apple juices has been developed. For this separation purpose, a monocationic imidazolium-based ionic liquid bearing a reactive terminal iodine atom was synthesized by a quaternization-anion exchange chemical sequence. Next, the gas chromatography (GC) stationary phase was prepared by covalently linking the imidazolium monolith to the reactive silanol groups of the inner capillary wall at 70 °C. This coated GC column exhibited g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…ILs containing imidazolium cations are generally the most widely examined IL-stationary phases; however, they are also among the most susceptible at undergoing decomposition/volatilization at elevated temperature. To further improve their thermal stability as well as the separation performance, Pello-Palma et al reported a covalently bonded IL-based GC stationary phase for the determination of volatile compounds in cider apple juices . The stationary phase was prepared by covalently reacting the imidazolium monolith to the free silanol groups within the inner capillary surface.…”
Section: Chromatographic and Electrophoretic Separationsmentioning
confidence: 99%
See 1 more Smart Citation
“…ILs containing imidazolium cations are generally the most widely examined IL-stationary phases; however, they are also among the most susceptible at undergoing decomposition/volatilization at elevated temperature. To further improve their thermal stability as well as the separation performance, Pello-Palma et al reported a covalently bonded IL-based GC stationary phase for the determination of volatile compounds in cider apple juices . The stationary phase was prepared by covalently reacting the imidazolium monolith to the free silanol groups within the inner capillary surface.…”
Section: Chromatographic and Electrophoretic Separationsmentioning
confidence: 99%
“…To further improve their thermal stability as well as the separation performance, Pello-Palma et al reported a covalently bonded IL-based GC stationary phase for the determination of volatile compounds in cider apple juices. 119 The stationary phase was prepared by covalently reacting the imidazolium monolith to the free silanol groups within the inner capillary surface. The developed IL stationary phase exhibited a thermal stability up to 290 fused-silica capillary to improve thermal stability.…”
Section: Et Al Employed the [C 6 Mim + ][Ntfmentioning
confidence: 99%
“…Based on this, the government entities encourage cider producers to maximize the potential of the cider and increase the production of apples and pears of regional varieties, which resulted in the construction of four new "sidrarias" and in the formation of a panel of tasters for the sensorial analysis of the product. The aroma and flavour of apple ciders rely on the quality of the apples used during cider-making, which is associated to several factors, namely cultivars diversity and geographical climatic conditions (Pello-Palma et al, 2017). The combination of the several factors influenced the final product with the release of volatile organic compounds (VOCs) that can be used for authentication purposes, having a considerable contribution on the aroma and flavour of ciders (Mangas, González, Rodríguez, & Blanco, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Apples are the most consumed fruits worldwide and grown especially in temperate regions. According to the literature, > 10,000 apple varieties are documented, resulting in an extensive range of properties namely resistance, sweetness, acidity and ripening [1]. The apples production in Madeira Island reached over 3300 tons per year and there are several varieties available, being apple tree from Malus domestica Borkh.…”
Section: Introductionmentioning
confidence: 99%
“…The quality of apples and their derivatives is the result of several factors, such as cultivars used and climatic conditions. Thus, comprehensive knowledge about the chemical composition of apple varieties and the effect of their blending is crucial for understanding which volatile organic compounds (VOCs) result in highquality processed products [1].…”
Section: Introductionmentioning
confidence: 99%